From adjacent activation in Escherichia coli and DNA cyclization to eukaryotic enhancers: the elements of a puzzle - Amouyal, Michèle (Frontiers in Genetics, 2014)
DNA cyclization, E. coli lac repressor binding to two spaced lac operators and repression enhancement can be successfully used for a better understanding of the conditions required for interaction between eukaryotic enhancers and the machinery of transcription initiation. Chronologically, the DNA looping model has first accounted for the properties initially defining enhancers, i.e. independence of action with distance or orientation with respect to the start of transcription. It has also predicted enhancer activity or its disruption at short distance (site orientation, alignment between promoter and enhancer sites), with high-order complexes of protein, or with transcription factor concentrations close or different from the w.t. situation. In another step, histones have been introduced into the model to further adapt it to eukaryotes. They in fact favor DNA cyclization in vitro. The resulting DNA compaction might explain the difference counted in base pairs in the distance of action between eukaryotic transcription enhancers and prokaryotic repression enhancers. The lac looping system provides a potential tool for analysis of this discrepancy and of chromatin state directly in situ. Furthermore, as predicted by the model, the contribution of operators O2 and O3 to repression of the lac operon clearly depends on the lac repressor level in the cell and is prevented in strains overproducing lac repressor. By extension, gene regulation especially that linked to cell fate, should also depend on transcription factor levels, providing a potential tool for cellular therapy. In parallel, a new function of the O1-O3 loop completes the picture of lac repression. The O1-O3 loop would at the same time ensure high efficiency of repression, inducibility through the low-affinity sites and limitation of the level of repressor through self-repression of the lac repressor. Last, the DNA looping model can be successfully adapted to the enhancer auxiliary elements known as insulators.